Study on synthesis and ring opening of cis-1-tosyl-2-tosylmethyl-3-(trifluoromethyl)-aziridine - Thắm, Phạm Thị; Chính, Phạm Thế; Anh, Đặng Thị Tuyết; Thuận, Ngô Thị; Tuyến, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
An efficient and straight forward approach towards the synthesis of cis-1-tosyl-2-tosyloxymethyl-3-(trifluoromethyl)aziridine 6 starting from ethyl triflouroacetaldehyde hemiacetal via imination, ring closure, hydride reduction, and hydrogenolysis was developed. The 2-(trifluoromethyl)aziridine compounds were obtained in a good yield. Cis-1-tosyl-2-tosyloxymethyl-3-(trifluoromethyl)aziridine 6 holds promising potential as a novel synthon for the preparation of a variety of nitrogen-containing target compounds upon selective manipulation of the reactive sites. Therefore, the reactivity ring opening of aziridine 6 was explored with mononucleophilic reagent. The structure of products were elucidated by the NMR, IR and MS spectrocopy